2018
DOI: 10.5130/ajceb.v18i1.5604
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Construction Tender Price Index in Ghana using Autoregressive Integrated Moving Average with Exogenous Variables Model

Abstract: Prices of construction resources keep on fluctuating due to unstable economic situations that have been experienced over the years. Clients knowledge of their financial commitments toward their intended project remains the basis for their final decision. The use of construction tender price index provides a realistic estimate at the early stage of the project. Tender price index (TPI) is influenced by various economic factors, hence there are several statistical techniques that have been employed in forecastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(56 reference statements)
0
1
0
1
Order By: Relevance
“…The use of VEC models to anticipate construction material prices lled a gap in the current literature caused by the necessity of forecasting both short and long-term movements of particular construction materials being overlooked. Kissi et al (2018) modelled the tender price index (TPI), in Ghana using an autoregressive integrated moving average with exogenous factors. The results showed that the ARIMAX model outperformed the single method in terms of predictive ability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of VEC models to anticipate construction material prices lled a gap in the current literature caused by the necessity of forecasting both short and long-term movements of particular construction materials being overlooked. Kissi et al (2018) modelled the tender price index (TPI), in Ghana using an autoregressive integrated moving average with exogenous factors. The results showed that the ARIMAX model outperformed the single method in terms of predictive ability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untuk itu diperlukan pedoman dasar perhitungan harga satuan yaitu analisa biaya dalam proyek konstruksi yang sering disebut dengan Analisa Harga Satuan Pekerjaan (AHSP) [14] [15]. Analisa harga satuan pekerjaan ini dipengaruhi oleh angka koefisien yang menunjukkan nilai bahan material, tenaga kerja, peralatan, dan waktu pengerjaan proyek yang dapat digunakan sebagai acuan untuk merencanakan suatu pekerjaan [16] [17].…”
Section: A R T I C L E I N F O Abstract Article Historyunclassified